Comparative Analysis of Welding Processes Using Different Thermoplastics - Trindade, Adelino; Guimarães, André (International Journal of Integrated Engineering, 2024)
This study examined and contrasted three widely utilized welding techniques for modern thermoplastics: hot gas welding, laser beam welding, and friction stir welding. These techniques were employed to join various thermoplastic materials, particularly focusing on polypropylene, polyethylene, and polyvinyl chloride. The weld quality was evaluated using visual inspections and tensile strength tests. Additionally, Vickers hardness tests were performed on the welded joints to detect microstructural alterations. The research aimed to deepen the understanding of the mechanisms behind these welding processes and assess the welded joints' strength.